Storytelling: Transdisziplinäre Erzählweisen zwischen Design, Kunst, Medienkultur und ästhetischer Tradition (Bewegtbilder, 2024)
Narratives have always shaped human experience. As a universal, cross-cultural practice, they have accompanied human history and reflect the diverse attempts to describe life and create meaning. From the earliest oral traditions to modern, technology-based media, stories shape our understanding of the world. A modern and integrative concept of storytelling refers equally to the use of static and dynamic media forms. The presentation and reception situations of these - sometimes multimodal - media also influence the specific forms of storytelling. Media shape the range and scope of the narrative. The contributors to this volume therefore explore the question of which possible forms and interpretations transdisciplinary storytelling encompasses and how this concept can be made useable for an aesthetic perspective.